Answer:
The value of the given expression at x = 3 is -2.
Step-by-step explanation:
This is a relatively easy question and we have to find the value of the given expression at a specific value of x. Here we have to be careful while solving the equation and make sure that there are calculation mistakes.
Also we can simplify the given equation once more and then substitute the value of x.
The given expression is [tex]2(x - 4) + 3x - x^2[/tex]
We have to find the value of this expression at x = 3.
[tex]2(x - 4) + 3x - x^2[/tex] = [tex]2(3 - 4) + 3\times 3 - 3^{2}[/tex]
= -2 + 9 - 9
= -2
The value of the given expression at x = 3 is -2.